The Effectiveness of Interactive Multimedia to Improve Cognitive Skill on Elementary School Students - Anggi Tiarasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to develop interactive multimedia to support thematic learning in elementary schools. The main results of the study are interactive multimedia products that are expected to be learning media to support the improvement of students' cognitive skills. This study was a Research and Development (R & D) study. The subject of this study was elementary school students. The data collection included: interviews, observations, tests of cognitive skills (pre-test and post-test), student responses, and documentation. The results of the study can be concluded that: students' responses to the development of interactive multimedia at the field testing stage are 80.24% and are included in the good and feasibility category; student learning outcomes in the testing phase of the main fields before and after the use of interactive multimedia increase. Moreover, based on the t-test the results are 101,333. So that it can be concluded that multimedia learning developed meets the requirements for teaching and learning.